Clinical application of transcranial magnetic stimulation for functional bowel disease - Li, Guangyao; Jin, Binghui; Fan, Zhe (Frontiers in Medicine, 2023)
Functional bowel disorder (FBD) is a common gastrointestinal disease syndrome characterized by dysmotility and secretion without known organic lesions. The pathogenesis of FBD is still unclear. In recent years, with the rise of neurogastroenterology, it has initially revealed its close relationship with the “brain-gut axis.” Transcranial magnetic stimulation (TMS) is a technique for detecting and treating the nervous system, that is characterized by non-invasiveness and painlessness. TMS plays an important role in the diagnosis and treatment of diseases, and provides a new method for the treatment of FBD. In this paper, we summarized and analyzed the research progress of using TMS therapy applied to patients with irritable bowel syndrome and functional constipation by domestic and foreign scholars in recent years by means of literature search, and found that TMS therapy could improve the intestinal discomfort and accompanying mental symptoms in patients with FBD.